Hospitality and compassion: the work and ethics of catholic chaplains supporting seafarers - Montemaggi, Francesca E. S. (Journal of beliefs and values, 2018)
This article opens a window on the world of chaplains supporting seafarers, which has largely been neglected by the literature. Shipping happens in ports, which are often far away from urban centres. It is thus removed from everyday experience making seafarers an invisible population and, with them, the chaplains who assist them. The article proposes to view chaplains' service to seafarers as a form of 'embodied' hospitality. It is an offer of a relationship as well as of assistance. The angle of hospitality sheds light on the dynamics of the relationships between seafarers and chaplains, the tensions and opportunities for exchange. The ethic of chaplains' hospitality that emerges from the observation and interviews is one of 'compassion' requiring openness to and acceptance of the other. Compassion, here, is the recognition of the dignity of the other based on a shared humanity.